Macromolecular shape and interactions in layer-by-layer assemblies within cylindrical nanopores - Lazzara, Thomas D.; Lau, K. H. Aaron; Knoll, Wolfgang; Janshoff, Andreas; Steinem, Claudia (Beilstein Journal of Nanotechnology, 2012)
Layer-by-layer (LbL) deposition of polyelectrolytes and proteins within the cylindrical nanopores of anodic aluminum oxide (AAO) membranes was studied by optical waveguide spectroscopy (OWS). AAO has aligned cylindrical, nonintersecting pores with a defined pore diameter d0 and functions as a planar optical waveguide so as to monitor, in situ, the LbL process by OWS. The LbL deposition of globular proteins, i.e., avidin and biotinylated bovine serum albumin was compared with that of linear polyelectrolytes (linear-PEs), both species being of similar molecular weight. LbL deposition within the cylindrical AAO geometry for different pore diameters (d0 = 25–80 nm) for the various macromolecular species, showed that the multilayer film growth was inhibited at different maximum numbers of LbL steps (nmax). The value of nmax was greatest for linear-PEs, while proteins had a lower value. The cylindrical pore geometry imposes a physical limit to LbL growth such that nmax is strongly dependent on the overall internal structure of the LbL film. For all macromolecular species, deposition was inhibited in native AAO, having pores of d0 = 25–30 nm. Both, OWS and scanning electron microscopy showed that LbL growth in larger AAO pores (d0 > 25–30 nm) became inhibited when approaching a pore diameter of deff,n_max = 25–35 nm, a similar size to that of native AAO pores, with d0 = 25–30 nm. For a reasonable estimation of deff,n_max, the actual volume occupied by a macromolecular assembly must be taken into consideration. The results clearly show that electrostatic LbL allowed for compact macromolecular layers, whereas proteins formed loosely packed multilayers.
Keywords: avidin-biotin; dendrimers; nanoporous substrates; optical lightmode waveguide spectroscopy; polyelectrolytes